Human Capital and Policies on Professional Development of Islamic Education Teachers at the Department of Ministry Religion Affair Yogyakarta - Munajat, Nur; Achmad, Arif Aryadi (Jurnal Pendidikan Islam, 2018)
This research was aimed to identify the relevance of human capital concepts with policies on the professional development of Islamic education teachers at the Department of Religion Yogyakarta. It was a qualitative study whose subject was the PAIS section and teachers of Islamic education in Yogyakarta. The results showed that the relevance of the human capital concept with the policies on the professional development of Islamic education teachers accounts for the design of some event programs conducted by PAIS (School Islamic Education Institution) section and POKJAWAS through yearly cooperative meetings. These programs were aimed to develop Islamic education teachers — these programs targeted their knowledge, skills, and capability. The teachers of Islamic education become an outstanding resource in performing their profession as teachers of Islamic education.